1988
DOI: 10.1093/oxfordjournals.eurheartj.a062444
|View full text |Cite
|
Sign up to set email alerts
|

Respective role of sympathetic tone and of cardiac pauses in the genesis of 62 cases of ventricular fibrillation recorded during Holter monitoring

Abstract: Sixty-two Holter recordings of sudden death due to ventricular fibrillation (VF) were analysed by full disclosure and computerized processing. Thirteen sudden deaths were due to torsades de pointes in noncoronary subjects (11/13), related to quinidine-like drugs and/or hypokalaemia: they were always initiated by a long RR cycle due to a post-extrasystolic pause, and announced by a progressive decrease of mean heart rate (from 77.5 +/- 2.5 to 60.6 +/- 2.7 beats min-1, P less than 0.001), in the three preceding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…In patients with structural heart disease or Brugada syndrome, 2 studies showed that spontaneous initiation of VF was preceded in 67% of episodes by isolated premature beats that were identical to the triggering beat. 34,35 Decreasing the incidence of VF with localized ablation may reduce defibrillation requirement and replacement and improve the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with structural heart disease or Brugada syndrome, 2 studies showed that spontaneous initiation of VF was preceded in 67% of episodes by isolated premature beats that were identical to the triggering beat. 34,35 Decreasing the incidence of VF with localized ablation may reduce defibrillation requirement and replacement and improve the patient's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies [60,61] observed that there were three major time periods when a cardiac arrest was most likely to occur-an early peak in the morning around 1100 hours, a late peak in the evening around 2200 hours, and, for those whose arrest was from a cardiac disease, a third time period-around 1600 hours-also seemed to be critical. In Seattle [62] and Berlin [63], the most important times for a cardiac arrest seemed to be around 1000 and 1800 hours. Ventricular fibrillation was most frequent around 2000 hours in the series by Peckova et al [60,64], while Arntz and associates found that ventricular fibrillation occurred most often around 1000 hours, with the exception of ventricular fibrillation, the circadian variation of the arrest rhythm in both cardiac and non-cardiac groups appeared to be identical.…”
Section: Mechanisms Underlying Sudden Cardiac Deathmentioning
confidence: 99%
“…10,11 Outside the acute phase of the AMI, documentation comes from 24-to 48-hour Holter recordings obtained at randomly selected intervals, [12][13][14] leaving large gaps in the temporal knowledge of arrhythmia incidence in these patients. Prospective studies using long-term ECG monitoring in consecutive patients surviving AMI have not been performed.…”
Section: Editorial See P 1255 Clinical Perspective On P 1264mentioning
confidence: 99%